'Getting back to normality seems as big of a step as going into lockdown': the impact of the COVID-19 pandemic on people with early to middle stage dementia. (22nd January 2021) - Talbot, Catherine V; Briggs, Pam
Abstract: People with dementia can experience shrinkage of their social worlds, leading to a loss of independence, control and reduced well-being. We used 'the shrinking world' theory to examine how the COVID 19 pandemic has impacted the lives of people with early to middle stage dementia and what longer-term impacts may result. Interviews were conducted with 19 people with dementia and a thematic analysis generated five themes: the forgotten person with dementia, confusion over government guidance, deterioration of cognitive function, loss of meaning and social isolation, safety of the lockdown bubble. The findings suggest that the pandemic has accelerated the 'shrinking world' effect and created tension in how people with dementia perceive the outside world. Participants felt safe and secure in lockdown but also missed the social interaction, cognitive stimulation and meaningful activities that took place outdoors. As time in lockdown continued, these individuals experienced a loss of confidence and were anxious about their ability to re-engage in the everyday practises that allow them to participate in society. We recommend ways in which the government, communities and organisations might counteract some of the harms posed by this shrinking world.